The Impact of Village Funds on The Indonesian Economy: Expansion and Progress - Sofyana, Sofyana; Manan, Afni Abdul; Ardiansyah, Ardiansyah; Aprilya, Indriyani; Riyanti, Riyanti (Teunuleh Publisher, 2025)
This study examines the impact of village fund allocations on economic growth and development in Indonesia within the decentralized development framework. Indonesia’s economic progress remains less inclusive, hindered by infrastructure disparities and centralized development legacies. To address regional inequalities, the government implemented village funds since 2015, aiming to spur rural development. Using a quantitative approach, this research applies the Difference-in-Difference (DID) method to analyze panel data from Indonesian districts and cities between 2011 and 2019. The study compares treatment areas receiving village funds to control areas without such funding, controlling for infrastructure, population, poverty, education, and other socioeconomic factors. Findings reveal that village fund allocations positively and significantly contribute to economic growth and development indicators, reflected in improved infrastructure and increased economic activities, such as the proliferation of Village-Owned Enterprises (BUMDes). Although the impact is statistically significant, it remains relatively modest, suggesting room for improved fund utilization and distribution mechanisms. The research highlights the need for continued provision of village funds alongside enhanced accountability to maximize developmental benefits. This study addresses a critical aspect of Indonesia’s inclusive growth agenda, demonstrating the role of decentralized funding in rural economic empowerment. The robust methodological approach and empirical evidence support policy recommendations for sustaining and optimizing village fund programs to foster balanced regional development nationwide.